Opsonization and Phagocytosis of Plasmodium falciparum Merozoites Measured by Flow Cytometry - Kumaratilake, Lakshmi M. (American Society for Microbiology, 2000)
A flow cytometric phagocytosis assay was established to investigate the role of anti-merozoite antibody, complement, and cytokines on the phagocytosis of Plasmodium falciparum merozoites by human neutrophils. This assay involved allowing fluorescein isothiocyanate-labeled merozoites to interact with phagocytes and analysis of the cells on a FACScan with Lysis II software. To differentiate the proportion of neutrophil surface-bound merozoites from the merozoites ingested by neutrophils, the fluorescence of bound merozoites was quenched by adding trypan blue. The data showed that sera from malaria-immune individuals in the Solomon Islands and Papua New Guinea promoted merozoite engulfment by neutrophils. The cytokines tumor necrosis factor alpha, gamma interferon, granulocyte-macrophage colony-stimulating factor, and interleukin-1β significantly increased the amount and the rate of merozoite phagocytosis by neutrophils. Optimum merozoite phagocytosis occurred when both cytokines and anti-malarial antibody were present.